KEAMANAN DAN RISIKO DALAM TRANSAKSI UANG DIGITAL : STUDI PADA PLATFORM E-WALLLET DI INDONESIA - Rima Mutia; Muhammad Irwan Fadli Nasution (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Abstract The development of digital technology has brought significant changes to the payment system in Indonesia, especially through the use of electronic money and digital wallets (e-wallets). Although the use of e-wallets is convenient and effective in conducting cashless transactions, there are many challenges regarding security and risks for users. The aim of this research is to examine the security and risks of digital currency transactions on e-mobile platforms in Indonesia, with a focus on technical issues and data security threats. The development of digital technology has brought significant changes to the payment system in Indonesia, especially through the use of electronic money and digital wallets (e-wallets). Although the use of e-wallets is convenient and effective in conducting cashless transactions, there are many challenges regarding security and risks for users. The aim of this research is to examine the security and risks of digital currency transactions on e-mobile platforms in Indonesia, with a focus on technical issues and data security threats. The research results show that although most users feel safe using e-wallets due to security features such as PIN, biometric authentication and OTP, the threat of phishing and hacker attacks is the biggest problem they face. In addition, technical problems such as system failures can affect users' comfort and trust in this platform. The study concluded that efforts to increase digital literacy and educate users about online security are important to reduce the risk of fraud and data theft when using e-banking. Additionally, e-mobile providers must continue to develop security features to protect users from newer cyber threats. Keywords: e-wallet, security, risk Abstrak Perkembangan teknologi digital telah membawa perubahan signifikan pada sistem pembayaran di Indonesia, khususnya melalui penggunaan uang elektronik dan dompet digital (e-wallet). Meskipun penggunaan dompet elektronik nyaman dan efektif dalam melakukan transaksi non tunai, terdapat banyak tantangan terkait keamanan dan risiko bagi pengguna. Tujuan dari penelitian ini adalah untuk mengkaji keamanan dan risiko transaksi mata uang digital pada platform e-mobile di Indonesia, dengan fokus pada permasalahan teknis dan ancaman keamanan data. Hasil penelitian menunjukkan bahwa meskipun sebagian besar pengguna merasa aman menggunakan dompet elektronik karena fitur keamanan seperti PIN, otentikasi biometrik, dan OTP, ancaman serangan phishing dan peretas adalah masalah terbesar yang mereka hadapi. Selain itu, masalah teknis seperti kegagalan sistem dapat mempengaruhi kenyamanan dan kepercayaan pengguna terhadap platform ini. Studi tersebut menyimpulkan bahwa upaya meningkatkan literasi digital dan mengedukasi pengguna tentang keamanan online penting dilakukan untuk mengurangi risiko penipuan dan pencurian data saat menggunakan e-banking. Selain itu, penyedia e-mobile harus terus mengembangkan fitur keamanan untuk melindungi pengguna dari ancaman dunia maya yang lebih baru. Kata Kunci: e-wallet, keamanan, risiko